2011
DOI: 10.1155/2011/890308
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Weight Change in Male HIV-Positive Injection Drug Users Initiating Antiretroviral Therapy in Hanoi, Vietnam

Abstract: We examined clinical and nutritional predictors of weight change over two consecutive 6-month intervals among 99 HIV-positive male injection drug users initiating antiretroviral therapy (ART) in Hanoi, Vietnam. The average weight gain was 3.1 ± 4.8 kg in the first six months after ART and 0.8 ± 3.0 kg in the following six months. Predictors of weight change differed by interval. In the first interval, CD4 < 200 cells/μL, excellent/very good adherence to ART, bothersome nausea, and liquid supplement use were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
3
11
0
1
Order By: Relevance
“…It was found that several significant predictors of weight gain, particularly in the first six months after ART initiation. Patients with more advanced HIV infection at baseline (CD 4 cell counts <200 cells/μl) were more likely to have positive weight changes (54 to 61 kg) in the first six months of therapy than the other, likely due to the beneficial effects of ART, which is similar to the above study 32 , while patients receiving ART whose CD 4 cell count > 350 cells/ µl patient had the least weight improvement from 56 kg to 59 kg this may due to they had good immune system. The average weight gain over the 24 months was 6 kg this is higher when compared with study conducted by Ross-Degnan et al and BMC Health services research both research stated that patients gained an average of 3.9 kg in the first six months of treatment 22 .…”
Section: Discussionsupporting
confidence: 70%
“…It was found that several significant predictors of weight gain, particularly in the first six months after ART initiation. Patients with more advanced HIV infection at baseline (CD 4 cell counts <200 cells/μl) were more likely to have positive weight changes (54 to 61 kg) in the first six months of therapy than the other, likely due to the beneficial effects of ART, which is similar to the above study 32 , while patients receiving ART whose CD 4 cell count > 350 cells/ µl patient had the least weight improvement from 56 kg to 59 kg this may due to they had good immune system. The average weight gain over the 24 months was 6 kg this is higher when compared with study conducted by Ross-Degnan et al and BMC Health services research both research stated that patients gained an average of 3.9 kg in the first six months of treatment 22 .…”
Section: Discussionsupporting
confidence: 70%
“…among adult receiving ART in Vietnam (Table 4). The proportion of viral suppression (< 1,000 copies/ml) at 6 and 12 month since ART initiation among IDU who were recruited from a treatment site in Ha Noi in 2006-2008, was of 74% and 68%, respectively [42]. This figure was likely to be substantially lower than of that of an average people receiving ART.…”
Section: Risks Factors For Emergence and Transmission Of Hiv Drug Resmentioning
confidence: 88%
“…Non-adherence is caused by numerous factors. Most adults on ART were IDU (62%) [24], whose high level of active illicit drug use during therapy (30-33%) [42], directly impacts on their adherence to ARV drugs. Furthermore, widespread stigma and discrimination related to HIV infection leads to a fear of disclosure of their HIV positive status and use of ART [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HFIAS has been used in several HIV cohorts in the US [47,48], and among HIV-positive populations in Zambia, Uganda and Kenya [49][50][51]. The Household Food Security Scale-Short Form (HFSS-SF) was recently applied in cohorts of PLHIV in Tanzania [52] and Vietnam [53].…”
Section: Food and Nutrition Scurity Measuresmentioning
confidence: 99%